Polyphyletic Nature of Salmonella enterica Serotype Derby and Lineage-Specific Host-Association Revealed by Genome-Wide Analysis - Sévellec, Yann; Vignaud, Marie-Léone; Granier, Sophie A.; Lailler, Renaud; Feurer, Carole; Le Hello, Simon; Mistou, Michel-Yves; Cadel-Six, Sabrina (Frontiers in Microbiology, 2018)
In France, Salmonella Derby is one of the most prevalent serotypes in pork and poultry meat. Since 2006, it has ranked among the 10 most frequent Salmonella serotypes isolated in humans. In previous publications, Salmonella Derby isolates have been characterized by Pulsed Field Gel Electrophoresis (PFGE) and antimicrobial resistance (AMR) profiles revealing the existence of different pulsotypes and AMR phenotypic groups. However, these results suffer from the low discriminatory power of these typing methods. In the present study, we built a collection of 140 strains of S. Derby collected in France from 2014 to 2015 representative of the pork and poultry food sectors. The whole collection was characterized using Whole Genome Sequencing (WGS), providing a significant contribution to the knowledge of this underrepresented serotype, with few genomes available in public databases. The genetic diversity of the S. Derby strains was analysed by single-nucleotide polymorphism (SNP). We also investigated antimicrobial resistance by both genome and phenotype, the main Salmonella Pathogenicity Island (SPI) and the fimH gene sequences. Our results show that this S. Derby collection is spread across four different lineages genetically distant by an average of 15k SNPs. These lineages correspond to four Multilocus Sequence Typing (MLST) types (ST39, ST40, ST71 and ST682), which were found to be associated with specific animal hosts: pork and poultry. While the ST71 and ST682 strains are pansusceptible, ST40 isolates are characterized by the multidrug resistant profile STR-SSS-TET. Considering virulence determinants, only ST39 and ST40 present the SPI-23, which has previously been associated with pork enterocyte invasion. Furthermore, the pork ST682 isolates were found to carry mutations in the fimH sequence that could participate in the host tropism of this group. Our phylogenetic analysis demonstrates the polyphyletic nature of the Salmonella serotype Derby and provides an opportunity to identify genetic factors associated with host adaptation and markers for the monitoring of these different lineages within the corresponding animal sectors. The recognition of these four lineages is of primary importance for epidemiological surveillance throughout the food production chains and constitutes the first step toward refining monitoring and preventing dispersal of this pathogen.